Real estate market risk in bank stock returns: evidence for 15 European countries - Martins, António Miguel; Serra, Ana Paula; Martins, Francisco Vitorino (International Journal of Strategic Property Management, 2016)
In countries with highly-developed financial systems bank portfolios have high exposure, directly or indirectly, to the real estate sector. Changes in the value of real estate can have a potentially significant impact on the default risk of banks and on their profitability as a result of high exposure to the real estate sector. This is especially critical during real estate crises, when bank losses tend to increase dramatically, placing the entire financial system at risk of collapse, as it was the case of the recent international subprime crisis. This article studies the sensitivity of bank stock returns to real estate returns in 15 European countries. The results indicate that bank stocks are sensitive to real estate market conditions. There is a positive relation between bank stock returns and real estate returns after controlling for general market conditions and interest rates changes.